2004
DOI: 10.1093/toxsci/kfh249
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Feed Restriction during in Utero and Postnatal Development in Rats

Abstract: This study determined the effects of feed restriction (FR) during in utero and postnatal life on standard reproductive toxicity and developmental immunotoxicity end points. Groups of 26 time-mated CD rats were fed various amounts of Purina 5002 diet from gestation day 7 through lactation. Control rats were fed once per day in amounts based on historical control feed consumption data, while the amounts fed to the FR groups were reduced by 10% (10% FR), 30% (30% FR), or 50% (50% FR) relative to controls. Selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 15 publications
3
33
3
1
Order By: Relevance
“…Maternal body weights at weaning were decreased by 12% and 27% relative to the control dams in the 100 and 200 ppm groups, respectively. In a previous study of the effects of feed restriction during the gestation and lactation periods in rats, body weights of dams were decreased by 1-5%, 10-20% and 17-32% in the 10%, 30% and 50% food restriction groups, respectively (Carney et al, 2004), and the body weight curves were similar to those for our ACRtreated dams. Since reduced body weight gain concomitant with reduced food and water consumption was apparent here, particularly in the later stages of the experimental period, it can be considered that the advanced neurotoxicity due to ACR led to maternal malnutrition.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Maternal body weights at weaning were decreased by 12% and 27% relative to the control dams in the 100 and 200 ppm groups, respectively. In a previous study of the effects of feed restriction during the gestation and lactation periods in rats, body weights of dams were decreased by 1-5%, 10-20% and 17-32% in the 10%, 30% and 50% food restriction groups, respectively (Carney et al, 2004), and the body weight curves were similar to those for our ACRtreated dams. Since reduced body weight gain concomitant with reduced food and water consumption was apparent here, particularly in the later stages of the experimental period, it can be considered that the advanced neurotoxicity due to ACR led to maternal malnutrition.…”
Section: Discussionsupporting
confidence: 82%
“…However, it has been reported that pup body weights were significantly decreased due to maternal malnutrition along with reduction of maternal body weight, food and water consumption in Wistar rats gavaged with ACR 25 mg/kg body weight/ day throughout lactation (Friedman et al, 1999). In addition, maternal food restriction during gestation and lactation suppresses pup body weight (Carney et al, 2004). Therefore, it is considered that the maternal malnutrition observed with ACR at ≥100 ppm could have greatly affected pup body weights in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…A previous feed restriction study with untreated rats showed weanling testes weights alter with decreased body weight (Carney et al 2004). In contrast, testes weights are conserved in the presence of similar/modest body weight decrements in adult male rats (Chapin et al 1993).…”
Section: Mammalian Studiesmentioning
confidence: 93%
“…As would be expected with endocrine disruption, ALoverfeeding had adverse effects on estrous cyclicity and onset of reproduction senescence in the SD females Merry et al, 1994;Keenan et al, 1995;McShane et al, 1996;Small et al, 2002;Pasquale et al, 2003;Rauser et al, 2003;Roy et al, 2003;Carney et al, 2004;Chiu et al, 1996). Since the stages of the polyestrous cycle in the rat can be classified by cell types present in vaginal lavage, and the cycle length is normally approximately 4 to 5 days, we monitored these parameters to determine the reproductive status of the unbred females on this study.…”
Section: Discussionmentioning
confidence: 91%